Static and stability analysis of partial slip texture multi-lobe journal bearings - Rao, T.V.V.L.N. (SAGE Publications Ltd, 2020)
This paper presents one-dimensional analysis of modified dynamic Reynolds equation derived for partial slip texture multi-lobe journal bearings. The novelty included in this study is the configuration of partial slip texture region on the bottom bearing lobe surface of a multi-lobe journal bearing under a constant vertical load. The nondimensional pressure and shear stress for steady-state and nondimensional pressure gradients for dynamic coefficients for each lobe with partial slip texture configuration are derived based on narrow groove theory. Linearized stability analysis is evaluated using infinitesimal perturbation method. Results of static and stability characteristics of partial slip texture multi-lobe (two-axial groove, elliptical, three-lobe and offset) journal bearings are presented. Partial slip texture configuration significantly enhances load capacity, coefficient of friction, and stability of two-lobe journal bearing. Â© IMechE 2019.